Studi Laboratorium Pengaruh Variasi Temperatur Pemanasan Karbon Cangkang Kelapa Sawit Dan Arang Batok Kelapa Terhadap Strenght Semen Pemboran - Novrianti Novrianti (Politeknik Akamigas Palembang, 2016)
Cementing is one of the important processes in the drilling. A good quality bonding of cement will be able to reduce the problems that often occur in drilling operations at the same time can prolong the oil- well lifetime. This study aimed to observe the effect of heating temperature variation oil palm shell carbon and coconut shell charcoal on the strength of cement. This study focuses on the compressive strength and shear bond strength which are the two parameters that reflect the quality of cement strength. Value compressive strength and shear bond strength is obtained from biaxial loading test. Before conducting the test, various samples of cement with different heating temperature variation of additive prepared for mixing, drying and hardening process. The results of the tests showed that the compressive strength and shear bond strength optimum for each additive obtained at temperatures of 700 oC. Compressive strength and shear bond strength of cement with the addition of charcoal additive is higher than the cement additive added carbon palm shell.